Van relativisme naar oordeelsvorming. Recente tendensen in de wetenschapsgeschiedschrijving - Jonker, Ed (Studium, 2011)
From relativism to evaluation. Recent trends in the historiography of science and the humanitiesHistorians of science have taken leave of finalism. No longer do they write teleological histories of scientific progress. Instead of a grand narrative on the triumph of science they now tend to write small stories on local knowledge. This is the result of several decades of criticism of Whig history. Starting with neo-marxist critique in the interwar years, enhanced in the social history of the 1970s, science was seen as an economic commodity and as a social product. Cultural history and anthropology added the view that scientists and scholars are mere mortals, muddling through messy life. This critique was topped off with postmodern criticism of knowledge as power, which translates into the accusation that historiography is only legitimating cultural and political oppression.To counter these allegations, many historians have insulated themselves into a kind of retro-historicism that shies away from any teleology, coherence, meaning and evaluation. It depicts the production of knowledge as a practical, local activity that is strictly limited to its cultural context. No claims to truth, validity, let alone progress or even development were allowed.This situation of rampant relativism could not last. Total abstinence of any evaluation of knowledge claims, quality of research or success of theories has proven unsatisfactory. The need has arisen to study broader issues of traveling knowledge and longer lines of scientific development. There is a shift of interest into traditions of knowledge that spring the bonds of locality and context. Why do some scientific theories and research practices succeed in surpassing paradigms and bridging epistemic ruptures? In this respect disciplines are in the process of being rehabilitated. Instead of oppressive structures they become the vehicles of sustained knowledge growth. Especially the role of education and academic training is focused on. Facing up to the charges of conceptual anachronism, historians of knowledge now opt for a cautiously evaluative history. The alternative would be an intellectually barren historicism.